Association between [Ga-68]NODAGA-RGDyK uptake and dynamics of angiogenesis in a human cell-based 3D model - Grönman Maria; Moisio Olli; Li Xiang-Guo; Toimela Tarja; Huttala Outi; Heinonen Tuula; Knuuti Juhani; Roivainen Anne; Saraste Antti (SPRINGER, 2022)
Radiolabeled RGD peptides targeting expression of alpha(v)beta(3) integrin have been applied to in vivo imaging of angiogenesis. However, there is a need for more information on the quantitative relationships between RGD peptide uptake and the dynamics of angiogenesis. In this study, we sought to measure the binding of [Ga-68]NODAGA-RGDyK to alpha(v)beta(3) integrin in a human cell-based three-dimensional (3D) in vitro model of angiogenesis, and to compare the level of binding with the amount of angiogenesis. Experiments were conducted using a human cell-based 3D model of angiogenesis consisting of co-culture of human adipose stem cells (hASCs) and of human umbilical vein endothelial cells (HUVECs). Angiogenesis was induced with four concentrations (25%, 50%, 75%, and 100%) of growth factor cocktail resulting in a gradual increase in the density of the tubule network. Cultures were incubated with [Ga-68]NODAGA-RGDyK for 90 min at 37 degrees C, and binding of radioactivity was measured by gamma counting and digital autoradiography. The results revealed that tracer binding increased gradually with neovasculature density. In comparison with vessels induced with a growth factor concentration of 25%, the uptake of [Ga-68]NODAGA-RGDyK was higher at concentrations of 75% and 100%, and correlated with the amount of neovasculature, as determined by visual evaluation of histological staining. Uptake of [Ga-68]NODAGA-RGDyK closely reflected the amount of angiogenesis in an in vitro 3D model of angiogenesis. These results support further evaluation of RGD-based approaches for targeted imaging of angiogenesis.